Phosphorylation of Y845 on the Epidermal Growth Factor Receptor Mediates Binding to the Mitochondrial Protein Cytochrome c Oxidase Subunit II - Boerner, Julie L. (American Society for Microbiology (ASM), 2004)
When co-overexpressed, the epidermal growth factor receptor (EGFR) and c-Src cooperate to cause synergistic increases in EGF-induced DNA synthesis, soft agar colony growth, and tumor formation in nude mice. This synergy is dependent upon c-Src-mediated phosphorylation of a unique tyrosine on the EGFR, namely, tyrosine 845 (Y845). Phenylalanine substitution of Y845 (Y845F) was found to inhibit EGF-induced DNA synthesis without affecting the catalytic activity of the receptor or its ability to phosphorylate Shc or activate mitogen-activated protein kinase. These results suggest that synergism may occur through alternate signaling pathways mediated by phosphorylated Y845 (pY845). One such pathway involves the transcription factor Stat5b. Here we describe another pathway that involves cytochrome c oxidase subunit II (CoxII). CoxII was identified as a specific binding partner of a pY845-containing peptide in a phage display screen. EGF-dependent binding of CoxII to the wild type but not to the mutant Y845F-EGFR was confirmed by coimmunoprecipitation experiments. This association also required the kinase activity of c-Src. Confocal microscopy, as well as biochemical fractionation, indicated that the EGFR translocates to the mitochondria after EGF stimulation, where it colocalizes with CoxII. Such translocation required the catalytic activity of the receptor but not phosphorylation of Y845. However, ectopic expression of the Y845F-EGFR prevented the EGF from protecting MDA-MB-231 breast cancer cells from adriamycin-induced apoptosis, whereas two mutants of Stat5b, a dominant-interfering mutant (DNstat5b) and a tyrosine mutation at 699 (Y699F-Stat5b) did not. Taken together, these data suggest that, through the ability of EGFR to translocate to the mitochondria, the binding of proteins such as CoxII to pY845 on the EGFR may positively regulate survival pathways that contribute to oncogenesis.